2020
DOI: 10.1002/hlca.202000175
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1,4‐Cyclohexadiene Carboxylates through a Formal [2+4]‐Cycloaddition of Propiolates under Cobalt Catalysis

Abstract: Dedicated to Prof. Antonio Togni on the occasion of his 65th birthday A low-valent cobalt(I) complex, formed from the reduction of CoBr 2 (dppe) with zinc, acts as catalyst for the efficient [2 + 4] cycloaddition of β-alkyl, cycloalkyl and aryl substituted propiolates to dienes. This transformation yields synthetically relevant 1,4-cyclohexadiene carboxylates in good to excellent yields. Furthermore, the target compounds are novel lead structures for the discovery of fragrance ingredients from the fruity, flor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Their odor characteristics have been proven to relate to the double bonds and substituents, but the study of 1,4-cyclohexadiene carboxylates is underdeveloped due to a lack of practical synthetic methods. In 2020, Goeke et al reported the Co-catalyzed formal [4 + 2] cycloaddition of 1,3-dienes and alkyl propiolates [ 56 ] ( Scheme 2 ). The obtained 1,4-cyclohexadiene carboxylates typically demonstrate fruity and green odors, which vary according to their substituents.…”
Section: Synthesis Of Fragrances Via Cycloaddition or Formal Cycloadd...mentioning
confidence: 99%
“…Their odor characteristics have been proven to relate to the double bonds and substituents, but the study of 1,4-cyclohexadiene carboxylates is underdeveloped due to a lack of practical synthetic methods. In 2020, Goeke et al reported the Co-catalyzed formal [4 + 2] cycloaddition of 1,3-dienes and alkyl propiolates [ 56 ] ( Scheme 2 ). The obtained 1,4-cyclohexadiene carboxylates typically demonstrate fruity and green odors, which vary according to their substituents.…”
Section: Synthesis Of Fragrances Via Cycloaddition or Formal Cycloadd...mentioning
confidence: 99%